A qualitative study on factors influencing older consumer dining out behaviour - Ganesan, L.; Abu Bakar, Ainul Zakiah; Othman, M. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Aging or growing old is an inevitable, rather than viewing this as another life stage, this transition period are not easily welcomed by many. The main reason is because with age we are getting more susceptible to disease and disability. This mind-set is changing slowly thanks to the progress in healthcare and government policy that not only care for their health but also helps the older people to lead a better life in their golden age. It is important to acknowledge this age group not just because they are living longer; it is also because they are getting bigger in size and economic power. The purpose of this study is to find out what would be the factor for older adults in Malaysia to dine out. Semi-structured in-depth interviews were done with Malaysian older people ages 55 and above (focusing mainly on those with education up to secondary school). 10 informers were interviewed for this study. The result of this study were analysed using the Atlas.ti software. Result of this study suggests that Malaysian older adults choose to dine out based on the cleanliness followed by food taste. This study will be beneficial in providing more insight to this untapped market segment.